Perbedaan Pengetahuan Kader Posyandu Sebelum dan Sesudah Dilakukan Pelatihan Penggunaan Aplikasi iPOSYANDU - Widarti Widarti; Fedri R Rinawan; Ari Indra Susanti; Hironima N Fitri (Pengabdian dan Pengembangan Masyarakat Sekolah Vokasi UGM, 2018)
Posyandu cadres are community elements that have an important role in carrying out Posyandu activities. Cadre's tasks include registration, recording, weighing, counseling, and discussing the results of Posyandu activities. One important task of cadres is recording and reporting. So far, the recording and reporting of posyandu is still done manually, therefore cadres need to be supported by information technology to facilitate the task. The iPosyandu application is one of the smartphone application innovations that is used to facilitate cadre assignments in Posyandu activities. This study aims to determine the differences in knowledge of cadres before and after training about the use of iPosyandu applications. The research method used is analytical with cross sectional approach. The subjects of this study were 86. Posyandu cadres in Pasawahan District. Retrieval of data in this study using research instruments in the form of questionnaires given before and after training. The results of this study indicate that there are differences in Posyandu cadre knowledge before and after training, namely p = 0,000 (p <0.05). Cadres who have good knowledge increase up to 100%. Before the training, cadres who had good knowledge were 54.65%. Increased cadre knowledge score of 45.35%. The conclusion of this study is that there is a difference in cadre knowledge after training on the use of the iPosyandu application.